Illumination conditions within permanently shadowed regions at the lunar poles: Implications for in-situ passive remote sensing. (January 2021) - Kloos, Jacob L.; Moores, John E.; Godin, Paul J.; Cloutis, Ed
Abstract: Permanently shadowed regions (PSRs) at the lunar poles are of unique interest for science and exploration due to their low surface temperatures and potential for volatile sequestration. While not directly illuminated by the Sun, PSRs are exposed to faint sources of radiation such as starlight, Lyman alpha photons from the interplanetary medium, and sunlight scattered from the surrounding topography. These illumination sources are significant as they contribute to the thermal energy budget of PSRs, and also provide a photon source with which to observe areas otherwise obscured by shadow. In this work, we survey the illumination conditions from the aforementioned sources within northern and southern hemisphere PSRs at far ultraviolet (FUV), visible (vis) and infrared (IR) wavelengths. With respect to magnitude, it is shown that scattered sunlight is the brightest radiation source to reach the PSRs in the visible and IR spectral regimes. As well, we show that scattered sunlight contributes a considerable supply of FUV photons, and may exceed the interplanetary medium/starlight brightness in many PSR craters due to the temporal and spatial variance of scattered sunlight. This finding suggests a higher rate of photodesorption and lower adsorption residence times for water molecules than previously suggested, and, furthermore, indicates that this rate fluctuates diurnally, seasonally and geographically owing to the variability of the incoming solar flux. Large differences in the received solar energy are found between craters, with crater latitude and size being among the modulating influences. Within individual craters, strong spatial heterogeneities in scattered solar flux are found, with equator-facing PSR slopes receiving 40%–60% of the total energy of slopes oriented toward the pole. Finally, we show that the radiation available is sufficient to detect water ice using vis/FUV or vis/IR filter pairings, and such observations can be made with signal to noise > 10 with an FUV-sensitive camera; however, with more scattered solar photons available for IR imaging, higher signal to noise ratios can be attained with a vis/IR filter pairing. Highlights: Scattered sunlight is mapped within lunar PSRs at FUV, vis and IR wavelengths. As modeled, scattered sunlight supplies an appreciable flux of FUV photons to PSRs. FUV scattered solar irradiation will contribute to photodesorption in PSRs. The upwelling radiation from PSR surfaces is sufficient for water ice prospecting. Enhanced SNR can be attained with vis/IR filter pairing.